PENERAPAN ALGORITMA C4.5 DALAM MENGUKUR TINGKAT KEPUASAN NASABAH PADA PT BANK MUAMALAT INDONESIA KCU MEDAN BARU BERBASIS WEB - Azli, Putri; Jaya, Indra Kelana; Ambarita, Indah (Universitas Methodist Indonesia, 2023)
In the field of service providers, sharia banking and conventional banking have differences in their characteristics which lie in the practice of running business operations, where operations are based on sharia principles, and this principle is the main attraction for customers to utilize sharia bank services. Quality of service is a key factor that will become a competitive advantage in today's banking world. This happens because the bank as a service company has the characteristic of being easy to imitate a product that has been marketed. The measurement method for determining customer satisfaction at Bank Muamalat is by applying data mining, where customer data that makes transactions will be inputted into the system and then processed using the C4.5 method with predetermined criteria. Data mining is a process of finding meaningful relationships, patterns and trends by examining large sets of data stored in storage using pattern recognition techniques. According to Algorithm C4.5 is an algorithm used to form a decision tree.